SARS-CoV-2 Antibody Seroprevalence in Jakarta, Indonesia - Ariawan, Iwan; Jusril, Hafizah; N Farid, Muhammad; Riono, Pandu; Wahyuningsih, Wiji; Widyastuti, Widyastuti; Handayani, Dwi Oktavia T L; Wahyuningsih, Endang Sri; Daulay, Rebekka; Henderiawati, Retno; Malik, Safarina G; Noviyanti, Rintis; Trianty, Leily; Fadila, Nadia; Myint, Khin Saw Aye; Yudhaputri, Frilasita A.; Venkateswaran, Neeraja; Venkateswaran, Kodumudi; Udhayakumar, Venkatachalam; Hawley, William A.; Morgan, Juliette; Pronyk, Paul M (Kesmas, 2022)
The SARS-CoV-2 transmission dynamics in low- and middle-income countries remain poorly understood. This study aimed to estimate the SARS-CoV-2 antibodies seroprevalence in Jakarta, Indonesia, and to increase knowledge of SARS-CoV-2 transmission in urban settings. A population-based serosurvey among individuals aged one year or older was conducted in Jakarta. Employing a multistage sampling design, samples were stratified by district, slum, and non-slum residency, sex, and age group. Blood samples were tested for IgG against three different SARS-CoV-2 antigens. Seroprevalence was estimated after applying sample weights and adjusting for cluster characteristics. In March 2021, this study collected 4,919 respondents. The weighted estimate of seroprevalence was 44.5% (95% CI = 42.5-46.5). Seroprevalence was highest among adults aged 30-49 years, with higher seroprevalence in women and the overweight/obese group. Respondents residing in slum areas were 1.3-fold more likely to be seropositive than non-slum residents. It was estimated that4,717,000 of Jakarta's 10.6 million residents had prior SARS-CoV-2 infection. This suggests that approximately 10 infections were undiagnosed/underreported for every reported case. About one year after the first COVID-19 case was confirmed, close to half of Jakarta's residents have been infected by SARS-CoV-2.